The Effect of Small Games on Learning Overhead Serve and Receiving in Volleyball For Secondary School Students - Jameel, Auda; Laidh, Khlud (Journal of Physical Education, 2019)
The importance of research lies in the use of modern educational method to develop the basic skills of volleyball for secondary school students using small games to serve our children and our teachers to provide what is best and to suit the great development in the methods and methods used in the world. The researchers used the experimental method on (97) first grade students of Al Qenduck secondary school from second Khurk Baghdad educational directorate. The subjects were (24) students divided into two equal groups. The researchers concluded that small groups style has a positive effect on learning volleyball skills in first grade secondary school students.